Histopathological Study of Liraglutide on Renal Deterioration Progression Induced by Doxorubicin - Hayder Hussein Luaibi; Mustafa Ghazi Alabbassi; Israa Burhan Raoof (College of Pharmacy / Mustansiriyah University, 2019)
Podocyte injury is a major factor in many renal diseases leading to proteinuria that causes the risk of developing kidney deterioration. Glomerulosclerosis and tubulointerstitial fibrosis are the main histopathological feature as consequence of inflammation and apoptosis a result of   long period of tubular protein load. Liraglutide an incretin hormone (GLP-1) analogue has effective as glycemic control in patient with type 2 diabetes. In recent years, liraglutide appear protected mechanism against inflammation and apoptosis for many tissues through GLP-1 receptor (GLP-1R) activation unrelated with glycemic control.  36 animal Wister rats used in this experiment, first group include 12 rats set as control group received just the normal saline, while second group include 24 rats induced podocyte injury by doxorubicin single dose and third group treated either normal saline or liraglutide (200 µg /kg/day I.P) for 28 days.  Histopathological study is used to assess the protected effect of liraglutide on podocyte injury induced in male rats through three main histopathological changes (glomerulosclerosis, tubular damage, inflammatory infiltration) by Hematoxylin and eosin staining. In this study treatment group(C) with liraglutide appeared significant decreased (P< 0.05) in glomerulosclerosis, tubulointerstitial, and inflammatory infiltration after 28 day of treatment. In conclusion, liraglutide is effective in reducing inflammation and apoptosis which associate with chronic renal development as well as renoprotection by glycemic control which is indirectly effect.